STUDY OF STATISTICAL STABILITY AND FAST CHARACTERISTICS OF THE PROPOSED HASHING FUNCTION OF THE IMPROVED CRYPTOGRAPHIC MODULE IN INFORMATION AND COMMUNICATION SYSTEMS - SMIRNOVA, TETIANA; YAKYMENKO, NATALIIA; SMIRNOV, OLEKSII; POLISHCHUK, LIUDMYLA; SMIRNOV, SERHII (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The study of statistical stability and speed characteristics of the proposed hashing function of the advanced module of cryptographic protection of information, which by recording information about the user ID, session ID, sending time, message length and its serial number, as well as using a new session key for encryption , allows to ensure the confidentiality and integrity of data in information and communication systems management processes. The object of research is the process of ensuring the confidentiality of data in information and communication systems management systems based on cloud technologies. The subject is the study of statistical stability and speed characteristics of the proposed hashing function of the advanced module of cryptographic protection in information and communication systems. The purpose of this work is to study the statistical stability and speed characteristics of the proposed hashing function of the advanced module of cryptographic protection in information and communication systems for process control based on cloud technologies. To use this module effectively, it is important to choose crypto-resistant encryption and hashing methods, as well as secret key synchronization. Cryptoalgorithms resistant to linear, differential, algebraic, quantum and other known types of cryptanalysis can be used as encryption and hashing functions. An experimental study was conducted, which confirmed the crypto-resistance of the advanced algorithm to linear and differential cryptanalysis and determined that the speed of cryptographic data processing by the advanced method using the developed encryption function is 1.98 times higher than analogues, and the key generation speed 1.17 times compared to the generators used in particular in the selected prototype.
Keywords: statistical stability; speed characteristics; hashing function; cryptographic protection; information and communication system